Power Balancing Mechanism and Controller Design for the Single-Phase Cascaded H-bridge Multilevel DSTATCOM - Han, Yang (Elektronika ir Elektrotechnika, 2013)
The power balancing mechanism and the effective voltage balancing control algorithm are presented for the single-phase cascaded H-bridge multilevel DSTATCOM. The dc voltage balancing control for CHB-DSTATCOM is splitted into the average voltage controller and the voltage balancing controller, which are designed to regulate the active power flow between the CHB-DSTATCOM with the grid and to regulate active power flow among each inverter units, respectively. The effectiveness of the control algorithm is validated by the simulation results. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3246